Associação entre o consumo de álcool e a doença periodontal em um população no sul do Brasil - Cerezer, Débora Martins (2020)
Periodontitis is an infectious-inflammatory disease resulting from the interaction between dental biofilm and host susceptibility. This interaction is modulated by modifying factors that can alter the onset, progression and response to treatment, increasing susceptibility to periodontal disease. The high consumption of alcohol negatively affects other health problems, especially in some more vulnerable populations, such as those living in rural areas. However, there is little evidence about the association of alcohol with periodontitis in this population profile. Thus, this dissertation aims to assess the association between alcohol consumption and periodontitis in residents of a rural area in southern Brazil. A representative sample (N = 688) of a population located in the rural area of Rosário do Sul, Rio Grande do Sul, Brazil was evaluated between March 2015 and May 2016. Supra and subgingival periodontal data (IPV, ISG, FRP, PS , NIC) were collected from 6 sites of all teeth present by calibrated examiners. Information on alcohol exposure was collected through the Alcohol Use Disorders Identification Test (AUDIT). In the adjusted model, no association between alcohol and stage III or IV periodontitis was detected. According to the 2012 classification, risk drinkers and those who consumed more than 1 glass / day of alcoholic beverages were associated with severe periodontitis (OR= 1.88; 95% CI 1.05 to 3.36 and OR= 1.92; 95% CI 1.02 to 3.59, respectively). However, no association was observed when adjusted for the independent variables and number of teeth with CAL ≥ 5 mm. The excessive use of alcohol was not statistically significant associated with periodontitis.